Strategic Planning in the Age of Mobile Food Delivery Apps - Raad A. Shareef (Cihan University-Erbil Journal of Humanities and Social Sciences)
This study aims to examine the effect of strategic planning on businesses' performance in the context of companies that use mobile food delivery apps in Erbil. The research observes how the various components of strategic planning (mission and vision, internal and external factor analysis, implementation, controlling and evaluation strategy) relate with the performance of companies that use mobile food delivery platforms. A survey questionnaire was distributed among 95 managers and team supervisors of (Lezzoo, Talabat, Talabatey, and TipTop) and 72 valid responses were obtained (75.78% response rate). Data were analysed with SPSS (version 26) using descriptive analysis, factor analysis, correlation analysis, and regression analysis. These results indicate a positive and significant association between strategic planning variables and business performance, thus confirming the four hypotheses.